Prevalence of anxiety disorder among undergraduate medical students: a cross-sectional study - Subramanian, Janani; Shedole, Dayalaxmi T.; Dhadave, Meenakshi M.; Gududur, Ajay Kumar (International Journal Of Community Medicine And Public Health, 2025)
Background: It is widely acknowledged that medical colleges are stressful places that frequently have a detrimental impact on students academic performance, physical, mental health and psychological well-being. Depression, anxiety, stress, are very common among them. The objective of the study was to estimate the prevalence of anxiety disorder among undergraduate medical students, and to study the relation of anxiety disorders with sociodemographic factors. Methods: A cross-sectional, descriptive study was conducted among undergraduate medical students of Gulbarga Institute of Medical Sciences, Kalaburagi for 2 months from September to October 2024. For the study 600 students from 1st year to 4th year (final year) were selected using convenience sampling method using Google form. General anxiety disorder-7(GAD-7) was used for assessing the level of anxiety among undergraduate students. Results: Among 474 medical students who participated in our study, the prevalence of anxiety disorder was found among 171 students (36%). The prevalence of anxiety was more among students studying 1st year (43.5%), 4th year (41.4%) and low prevalence was seen among 2nd year students (30.2%). Among 171 students who were having anxiety disorder, 66% of students were having mild anxiety, 29% were having moderate anxiety and 4.70% were having severe anxiety. There was a significant association seen between anxiety disorder and some socio-demographic factors like family size and age. Conclusions: With regular psychiatric evaluation and counselling for medical students in the initial stage we can detect the presence of any mental disorders and provide them immediate treatment early.